Active and Covert Infections of Cricket Iridovirus and Acheta domesticus Densovirus in Reared Gryllodes sigillatus Crickets - Duffield, Kristin R.; Hunt, John; Sadd, Ben M.; Sakaluk, Scott K.; Oppert, Brenda; Rosario, Karyna; Behle, Robert W.; Ramirez, José L. (Frontiers in Microbiology, 2021)
Interest in developing food, feed, and other useful products from farmed insects has gained remarkable momentum in the past decade. Crickets are an especially popular group of farmed insects due to their nutritional quality, ease of rearing, and utility. However, production of crickets as an emerging commodity has been severely impacted by entomopathogenic infections, about which we know little. Here, we identified and characterized an unknown entomopathogen causing mass mortality in a lab-reared population of Gryllodes sigillatus crickets, a species used as an alternative to the popular Acheta domesticus due to its claimed tolerance to prevalent entomopathogenic viruses. Microdissection of sick and healthy crickets coupled with metagenomics-based identification and real-time qPCR viral quantification indicated high levels of cricket iridovirus (CrIV) in symptomatic populations, and evidence of covert CrIV infections in healthy populations. Our study also identified covert infections of Acheta domesticus densovirus (AdDNV) in both populations of G. sigillatus. These results add to the foundational research needed to increase our understanding of the pathology of mass-reared insects and ultimately develop the prevention, mitigation, and intervention strategies needed for economical production of insects as a commodity.